2022
DOI: 10.3390/ijms231911665
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae as a Model System for Eukaryotic Cell Biology, from Cell Cycle Control to DNA Damage Response

Abstract: The yeast Saccharomyces cerevisiae has been used for bread making and beer brewing for thousands of years. In addition, its ease of manipulation, well-annotated genome, expansive molecular toolbox, and its strong conservation of basic eukaryotic biology also make it a prime model for eukaryotic cell biology and genetics. In this review, we discuss the characteristics that made yeast such an extensively used model organism and specifically focus on the DNA damage response pathway as a prime example of how resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 233 publications
(252 reference statements)
0
8
0
Order By: Relevance
“…S. cerevisiae is an excellent model organism to study various aspects of DNA damage response, DNA repair pathways, and mechanisms of DNA damage induction by chemical agents [ 97 99 ]. Studies using either wild-type yeast or mutants devoid of As(III)/Sb(III) detoxification transporters Acr3 and Ycf1 revealed that both As(III) and Sb(III) exhibit genotoxic properties at subcytotoxic concentrations [ 62 , 68 ].…”
Section: How Arsenic and Antimony Cause Genotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…S. cerevisiae is an excellent model organism to study various aspects of DNA damage response, DNA repair pathways, and mechanisms of DNA damage induction by chemical agents [ 97 99 ]. Studies using either wild-type yeast or mutants devoid of As(III)/Sb(III) detoxification transporters Acr3 and Ycf1 revealed that both As(III) and Sb(III) exhibit genotoxic properties at subcytotoxic concentrations [ 62 , 68 ].…”
Section: How Arsenic and Antimony Cause Genotoxicitymentioning
confidence: 99%
“…Studies using either wild-type yeast or mutants devoid of As(III)/Sb(III) detoxification transporters Acr3 and Ycf1 revealed that both As(III) and Sb(III) exhibit genotoxic properties at subcytotoxic concentrations [ 62 , 68 ]. 1 h exposure to As(III) triggered phosphorylation of histone H2A on Ser129 (an equivalent of human γH2AX, which is a sensitive DNA damage marker also in yeast) [ 97 99 ], starting from 250 μM in wild type and 50 μM in the double mutant acr3 Δ ycf1 Δ [ 62 , 68 ]. For Sb(III), high levels of H2A phosphorylation were observed after 1–2 h treatment with 200–500 μM in ycf1 Δ cells [ 62 , 68 ].…”
Section: How Arsenic and Antimony Cause Genotoxicitymentioning
confidence: 99%
“…One non‐pathogenic yeast species in particular, Saccharomyces cerevisiae (budding yeast), is commonly used as a powerful model to uncover the molecular machinery responsible for fundamental processes underlying diverse eukaryotic biology, for example, cell cycle, autophagy, membrane trafficking, the ubiquitin–proteasome system, and so forth. (Finley et al., 2012 ; Feyder et al., 2015 ; Zimmerman et al., 2016 ; Vanderwaeren et al., 2022 ). Notably, budding yeast was used to discover ESCRTs (endosomal sorting complexes required for transport) and ALIX responsible for biogenesis of a subclass of EVs called exosomes (Baietti et al., 2012 ; Gurung et al., 2021 ; Hurley, 2010 ; Juan & Fürthauer, 2018 ) and to uncover the molecular network responsible for preventing proteotoxicity induced by heat stress (i.e., the heat shock response; Lindquist & Craig, 1988 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 h). They are extensively used as a model system for the wide type of eukaryotic cell biology studies (from cell cycle control to DNA damage response) [ 20 ]. They also do not raise ethical doubts compared to animal research.…”
Section: Introductionmentioning
confidence: 99%